Certification of Standard Reference Material 1976B. Issue 3 (12th August 2015) - Black, David R.; Windover, Donald; Mendenhall, Marcus H.; Henins, Albert; Filliben, James; Cline, James P.
Abstract : The National Institute of Standards and Technology (NIST) certifies a suite of Standard Reference Materials (SRMs) to address specific aspects of the performance of X-ray powder diffraction instruments. This report describes SRM 1976b, the third generation of this powder diffraction SRM. SRM 1976b consists of a sintered alumina disc, approximately 25.6 mm in diameter by 2.2 mm in thickness, intended for use in the calibration of X-ray powder diffraction equipment with respect to line position and intensity as a function of 2 θ -angle. The sintered form of the SRM eliminates the effect of sample loading procedures on intensity measurements. Certified data include the lattice parameters and relative peak intensity values from 13 lines in the 2 θ region between 20° and 145° using Cu Kα radiation. A NIST-built diffractometer, incorporating many advanced and unique design features was used to make the certification measurements.